A Case of a Giant Epiphrenic Esophageal Diverticulum - Yankov G. (Sciendo, 2020)
The esophageal diverticula are divided into pharyngoesophageal, parabronchial and epiphrenic. They could also be divided into congenital and acquired, true and false, pulsion and traction. Pulsion diverticula are usually formed in motor disorders of the esophagus, above the place of hypertension and uncoordinated peristalsis. They are pseudo-diverticula caused by increased intramural pressure, leading to herniation of the mucosa and submucosa through the focal areas of the esophageal wall. We present a 65-year-old woman who underwent left-sided transthoracic diverticulectomy, modified Heller esophagocardiomyotomy, and modified Belsey-Mark IV fundoplication due to a huge epiphrenic esophageal diverticulum.